Game-related enjoyment or personal pre-requisites – which is the crucial factor when using geogames to encourage adolescents to value local biodiversity. Issue 3 (3rd July 2018) - Schaal, Sonja; Otto, Siegmar; Schaal, Steffen; Lude, Armin
ABSTRACT: Geogames are mobile, location-based and location dependent games for devices like smartphones and tablets. As geogames are played outdoors they offer various possibilities for environmental education. The geogame entitled FindeVielfalt Simulation is a location dependent game, developed in the BioDiv2Go project, which provides sensory experiences, discovering local biodiversity and increasing biodiversity-related knowledge and attitudes toward nature. The aim of this study is to examine the predictive potential of game-related enjoyment and of personal prerequisites (such as general ecological behaviour) on outcomes measuring acquisition of knowledge and attitude. Hierarchical regressions are used to investigate the dependencies of the constructs. The results demonstrate that an increase in biodiversity-related knowledge is neither predicted by previous attitudes nor by game-related enjoyment. Every player within the game was able to learn irrespective of personal prerequisites or game-enjoyment. However, the results also demonstrate that an increase in attitude toward nature is significantly influenced by game-related enjoyment and general ecological behaviour, with game-related enjoyment being the stronger predictor.